Penerapan Simulasi PhET Sebagai Virtual Laboratorium Pada Materi Getaran, Gelombang Dan Bunyi Dalam Meningkatkan Pemahaman Konsep Dan Aktivitas Belajar Peserta Didik Kelas VIII SMP Negeri 3 Kupang - Kornelius Kristianto; Oktavianus Ama Ki`i; Egidius Dewa (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study aims to 1) find out how to improve students' concept understanding after using PhET simulation as a virtual practicum on vibration, wave and sound material in class VIII SMP Negeri 3 Kupang, 2) find out how students' learning activities after using PhET simulation as a virtual practicum on vibration, wave and sound material in class VIII SMP Negeri 3 Kupang. This research was conducted at SMP Negeri 3 Kupang. This type of research is descriptive quantitative with One-Group Pretest-postest Design method. The research sample was students of class VIII C which amounted to 27 students. Data collection techniques using tests totaling 5 items and observation techniques. The results showed that students' concept understanding increased with a Gain score of 0.54 on sufficient criteria and students' learning activities obtained a percentage of 73% with high criteria.